Perawatan Dan Perbaikan Fruit Elevator Pabrik Kelapa Sawit - Ismael Marjuki; Epriyandi Epriyandi; Rafly Miftakhul Sasti (Journal of Applied Mechanical Engineering and Renewable Energy, 2026)
The palm oil plantation and processing industry is a key industry for Indonesia's economy. Palm oil exports are an important source of foreign exchange earnings, and this industry provides employment opportunities for millions of Indonesians. According to data from the Indonesian Ministry of Agriculture, the total area of palm oil plantations in Indonesia currently reaches around 8 million hectares, twice the area in the early 2000s, with around 30% located on the island of Kalimantan. In an analysis of the factors affecting Indonesia's palm oil exports (Ditjenbun, 2018). This research method is a qualitative research that emphasizes more on the process and results, how a treatment and care occurs and how to handle it effectively. Conclusion, Preventive maintenance is carried out on bucket bolts, bucket chains, transmission chains, and buckets. Preventive corrective maintenance is carried out on gearboxes, transmission chains, sprocket bearings, buckets, and bucket chains. Preventive breakdown maintenance is carried out during the replacement of bucket chains, sprocket bearings, and transmission gears. There are various types of damage that commonly occur in Fruit Elevators, including: damage to buckets, sprocket bearings, gearboxes, oil seals, and bucket chains. The causes of damage generally come from wear and tear, lack of lubrication, or mechanical wear due to high workload. Daily, weekly, monthly, and annual maintenance has been carried out with respective procedures such as lubrication, component checks, replacement of spare parts, and overhaul. The implementation of this maintenance schedule has proven effective in reducing the frequency of damage. Component replacement history data shows that components such as liners, sprockets, buckets, and gearboxes have the highest damage rates, thus requiring special attention and periodic monitoring to prevent repeated damage.